IMPLEMENTASI PELAYANAN PUBLIK PEMBAYARAN PAJAK KENDARAAN BERMOTOR (PKB) DRIVE THRU DI KOTA MAKASSAR - Ulhaq. F, Diyah; Mahsyar, Abdul; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aims to analyze and describe the implementation of public services through SAMSAT Drive Thru in Makassar City and to find out the supporting and inhibiting factors for implementing public services through SAMSAT Drive Thru in Makassar City. This type of research uses a qualitative descriptive type of research. Data collection techniques using observations, interviews, and documentation related to the object being studied related to the Implementation of Drive Thru Motor Vehicle Tax Payments (PKB) in Makassar City. The number of informants in this study were 9 people. The results of the study show that: Communication, Resources, Disposition, and Bureaucratic structure it can be said that it is good in the Makassar City Regional SAMSAT. Supporting factors contained in the SAMSAT Drive Thru service are the existence of adequate facilities and infrastructure such as a suggestion box, competent human resources and information technology that uses an electronic file system and inhibiting factors contained in the SAMSAT Drive Thru service is not all types of four-wheeled vehicles can be served and the lack of socialization related Conclusion Drawing / Verification. Keywords : Implemenation, Public Service, SAMSAT Drive Thru